Global and regional estimates of the contribution of herpes simplex virus type 2 infection to HIV incidence: a population attributable fraction analysis using published epidemiological data. Issue 2 (February 2020) - Looker, Katharine J; Welton, Nicky J; Sabin, Keith M; Dalal, Shona; Vickerman, Peter; Turner, Katherine M E; Boily, Marie-Claude; Gottlieb, Sami L
Summary: Background: A 2017 systematic review and meta-analysis of 55 prospective studies found the adjusted risk of HIV acquisition to be at least tripled in individuals with herpes simplex virus type 2 (HSV-2) infection. We aimed to assess the potential contribution of HSV-2 infection to HIV incidence, given an effect of HSV-2 on HIV acquisition. Methods: We used a classic epidemiological formula to estimate the global and regional (WHO regional) population attributable fraction (PAF) and number of incident HIV infections attributable to HSV-2 infection by age (15–24 years, 25–49 years, and 15–49 years), sex, and timing of HSV-2 infection (established vs recently acquired). Estimates were calculated by incorporating HSV-2 and HIV infection data with pooled relative risk (RR) estimates for the effect of HSV-2 infection on HIV acquisition from a systematic review and meta-analysis. Because HSV-2 and HIV have shared sexual and other risk factors, in addition to HSV-related biological factors that increase HIV risk, we only used RR estimates that were adjusted for potential confounders. Findings: An estimated 420 000 (95% uncertainty interval 317 000–546 000; PAF 29·6% [22·9–37·1]) of 1·4 million sexually acquired incident HIV infections in individuals aged 15–49 years in 2016 were attributable to HSV-2 infection. The contribution of HSV-2 to HIV was largest for the WHO African region (PAF 37·1% [28·7–46·3]), women (34·8% [23·5–45·0]), individuals aged 25–49 years (32·4% [25·4–40·2]), and established HSV-2 infection (26·8% [19·7–34·5]). Interpretation: A large burden of HIV is likely to be attributable to HSV-2 infection, even if the effect of HSV-2 infection on HIV had been imperfectly measured in studies providing adjusted RR estimates, potentially because of residual confounding. The contribution is likely to be greatest in areas where HSV-2 is highly prevalent, particularly Africa. New preventive interventions against HSV-2 infection could not only improve the quality of life of millions of people by reducing the prevalence of herpetic genital ulcer disease, but could also have an additional, indirect effect on HIV transmission. Funding: WHO.